P16INK4a overexpression as a predictor of survival in ocular surface squamous neoplasia. Issue 6 (6th March 2018) - Chauhan, Sheetal; Sen, Seema; Sharma, Anjana; Kashyap, Seema; Tandon, Radhika; Bajaj, Mandeep S; Pushker, Neelam; Vanathi, Murugesan; Chauhan, Shyam S
Abstract : Aims: To evaluate the expression and methylation status of the p16 INK4a gene in early and advanced American Joint Committee on Cancer (AJCC) stages of ocular surface squamous neoplasia (OSSN) and to correlate its association with clinicopathological features and survival. Methods: Sixty-four (35 early and 29 advanced AJCC stage) patients with OSSN formed part of this study and were followed up for 36–58 (mean 48±3.6) months. Immunohistochemical expression of the p16 INK4a protein and methylation status of the p16 INK4a gene were determined by methylation-specific PCR. Results: Overexpression of p16 INK4a was observed in 18/64 (28%) and hypermethylation in 35/64 (54.7%) OSSN cases. A gradual significant increase in the expression of p16 INK4a (0%–48%, P=0.03) and decrease in its methylation (75%–16%, P=0.001) was observed with disease progression from early to advanced tumour stage. Overexpression of p16 INK4a was significantly associated with palpebral location and diffuse growth pattern in both early and advanced T stage. Hypermethylation of p16 INK4a was significantly associated with history of longer sunlight exposure in both early and advanced T stage of OSSN cases. In advanced T stage, p16 INK4a overexpression was associated with reduced disease-free survival (P=0.02) and poor prognosis (HR, 0.2; P=0.03). Conclusions: OSSN patients presenting at an advanced AJCC stage with p16 INK4a overexpression may require more aggressive treatment. Epigenetic inactivation of the p16 INK4a gene due to sunlight exposure could be responsible for pathogenesis of OSSN.